Activated carbon enhanced anaerobic digestion of food waste – Laboratory-scale and Pilot-scale operation. (May 2018) - Zhang, Le; Zhang, Jingxin; Loh, Kai-Chee
Graphical abstract: Highlights: Optimum adding dose of activated carbon (AC) was 15 g/L working volume to enhance AD. Adding AC significantly improved methane yield and process stability in 8 L digester. Color removal of liquid phase of digestate and sludge granulation were improved. Abundance of phyla Firmicutes and Elusimicrobia were enriched by 1.7–2.9 times by AC. Methane yield in 1000 L pilot-scale digester increased 41% by AC supplementation. Abstract: Effects of activated carbon (AC) supplementation on anaerobic digestion (AD) of food waste were elucidated in lab- and pilot-scales. Lab-scale AD was performed in 1 L and 8 L digesters, while pilot-scale AD was conducted in a 1000 L digester. Based on the optimal dose of 15 g AC per working volume derived from the 1 L digester, for the same AC dosage in the 8 L digester, an improved operation stability coupled with a higher methane yield was achieved even when digesters without AC supplementation failed after 59 days due to accumulation of substantial organic intermediates. At the same time, color removal from the liquid phase of the digestate was dramatically enhanced and the particle size of the digestate solids was increased by 53% through AC supplementation after running for 59 days. Pyrosequencing of 16S rRNA gene showed the abundance of predominant phyla Firmicutes, Elusimicrobia and Proteobacteria selectively enhanced by 1.7-fold, 2.9-fold and 2.1-fold, respectively. Pilot-scale digester without AC gave an average methane yield of 0.466 L⋅(gVS) −1 ⋅d −1 at a composition of 53–61% v/v methane. With AC augmentation, an increase of 41% in methane yield was achieved in the 1000 L digester under optimal organic loading rate (1.6 g VSFW ·L −1 ·d −1 ).